2018
DOI: 10.1111/bjop.12360
|View full text |Cite
|
Sign up to set email alerts
|

The richaredifferent: Unravelling the perceived and self‐reported personality profiles of high‐net‐worth individuals

Abstract: Beyond money and possessions, how are the rich different from the general population? Drawing on a unique sample of high-net-worth individuals from Germany (≥1 million Euro in financial assets; N = 130), nationally representative data (N = 22,981), and an additional online panel (N = 690), we provide the first direct investigation of the stereotypically perceived and self-reported personality profiles of high-net-worth individuals. Investigating the broad personality traits of the Big Five and the more specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…As hierarchical settings promote competition and reward superior competences, they are the natural habitats in which status can be obtained. Consistent with this idea, narcissism levels are elevated in wealthy individuals (Leckelt et al, 2019) and chief executive officers (CEOs; Rosenthal & Pittinsky, 2006).…”
Section: Rivalrymentioning
confidence: 86%
See 1 more Smart Citation
“…As hierarchical settings promote competition and reward superior competences, they are the natural habitats in which status can be obtained. Consistent with this idea, narcissism levels are elevated in wealthy individuals (Leckelt et al, 2019) and chief executive officers (CEOs; Rosenthal & Pittinsky, 2006).…”
Section: Rivalrymentioning
confidence: 86%
“…Narcissistic admiration can thus facilitate a rise in social status with minimal (if any) social costs and may render narcissists more likely to occupy pivotal positions in society in the long term. Narcissism levels are higher among successful artists (Zhou, 2017), wealthier individuals (Leckelt et al, 2019), CEOs in general (Chatterjee & Hambrick, 2007), and high-paid CEOs in particular (O’Reilly, Doerr, Caldwell, & Chatman, 2014), and U.S. presidents (Watts et al, 2013). Thus, narcissistic admiration may be advantageous in the environments revolving around status (e.g., personal distinction, public recognition).…”
Section: The Spin Modelmentioning
confidence: 99%
“…In addition to differences in job autonomy and demographic characteristics, millionaires might differ in other ways from the general population that could influence time use and happiness. Personality characteristics that predict wealth and/or are shaped by wealth (Leckelt et al, 2018) could help to explain why wealthy individuals engage in more active leisure. Investigating the moderating role of personality is a promising avenue for future research (see also Matz, Gladstone, & Stillwell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that higher SES individuals have strong feelings of psychological entitlement. Individuals who have high income (Foster et al, 2003), have high net worth (Leckelt et al, 2019), feel wealthy (Piff, 2014), or self-identify as rich or high SES (Cai et al, 2012; Zitek & Jordan, 2016) feel especially entitled (or have high levels of the broader construct of narcissism). Individuals whose parents had high incomes or wealth also exhibit particularly high levels of entitlement (Chabrol et al, 2009; Martin et al, 2016).…”
Section: Previous Research On Ses and Psychological Entitlementmentioning
confidence: 99%